Pemanfaatan Media Pembelajaran Berbasis ICT pada Lembaga Pendidikan Non-Formal TPQ - Muslih, Muslih (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2016)
It is the fact that technology has developed rapidly today. Such a development has influenced communication pattern among people, including communication in the field of education, particularly the process of instruction in a class between teacher and student. Audio visual aids began to be utilized to deliver educational messages. In this case, these audio visual aids were functionedÂ  not merely as device aids in education but more than that they can function as an effecitve educational message deliverer. To support the success of teaching and learning process in a class, the utilization of audio visual aids need to be maximized. The utilization of instructional media, especially the ones based on Information and Communication Technology (ICT) is a must and need to be adopted by all teachers today if they wish to have effective and efficient instructions. This is valid for not only teachers who work in formal educational institution like a school, but also for teachers working in non-formal educational institution such as educational park of the Quran (TPQ).